The Influence of the BOD`s characteristics toward corporate social responsibility: Study non financial and financial firms in Indonesia - Muhammad Taufik (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2021)
This paper addresses the relationship between independent directors, gender diversity, board of directors (BOD) size, BOD meeting, BOD tenure, BOD turnover, and BOD remuneration to corporate social responsibility (CSR). This research is an empirical analysis using resource dependence theory, which underlies BOD as a capital provider for companies to respond to community engagement. The research sample is a company listed on the Indonesia Stock Exchange for the 2016-2019 period which consists of 232 companies and 927 observations. It is revealed that independent directors and BOD size have a positive and significant effect on CSR, while gender diversity, BOD size, BOD meeting, BOD tenure, and BOD turnover are not able to influence CSR. Surprisingly, independent directors and BOD turnover have a negative and significant correlation with CSR in the context of financial companies. BOD in Indonesia does not consider CSR as part of a firm`s strategic policy and fails to demonstrate the existence of the firm as part of the social system. These findings serve as a significant feedback for regulators and firms. It is preferable that the regulators consider revising the implementation of CSR-related regulations, which only requires companies that engage in the natural resources business or activities related to the natural resources business to conduct corporate social and environmental responsibility (CSR) activities. Regulators also need to reconsider regulations on the standard number of women in BOD, requirement to increase the number of BOD, and the requirement to establish a CSR committee. Meanwhile, the company needs to improve the recruitment system for BOD candidates that pays attention to community engagement.